P-289 The Influence of ENPP1 Expression in Mucosal Tissues. (February 2017) - Curtis, Valerie; Wang, Ruth; Schwisow, Kayla; Lee, Scott; Colgan, Sean
Abstract : Background: Previous work has established that extracellular adenosine signaling is protective in mucosal inflammation and promotes the resolution of ongoing inflammation. The sources of extracellular adenosine include enzymatic processing from nucleotides, such as ATP and AMP, which can be liberated from a variety of cell types, including leukocytes. ENPP1 is a type II transmembrane glycoprotein that can hydrolyze ATP and diadenosine triphosphate (Ap3A) to AMP and inorganic phosphate. ENPP1, present on the surface of chondrocytes, has been extensively studied for its role in tissue mineralization. Its potential role in the resolution of mucosal inflammation via AMP generation has yet to be determined. Methods: Guided by a microarray screen of hypoxia-inducible genes in mucosal epithelial cells, we identified the strong induction of ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) in a time-dependent manner. Presently, we have established that ENPP1 mRNA is expressed in T84 and Caco2 intestinal epithelial cells, and this expression can be upregulated by conditions that drive epithelial metabolism (e.g., exposure to the short chain fatty acid butyrate). Results: Likewise, studies in mouse intestinal epithelial cells lacking the transcription factor HIF-1a revealed significantly diminished expression of ENPP1. In parallel, it was revealed that activated human neutrophils are a source of Ap3A, previously thought to be made primarily by platelets. Conclusions: These studies indicate that Ap3A and ENPP1 at the mucosal surface may function to provide an additional source of adenosine, sub-serving its role in inflammatory resolution.